2006
DOI: 10.1016/j.apsoil.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high application rates of polyacrylamide on microbial metabolic potential in an agricultural soil

Abstract: Water soluble anionic polyacrylamide (PAM) is a highly effective erosion preventing and infiltration enhancing polymer, when applied at rates of 1-10 g 111-3 in furrow irrigation water. PAM greatly reduces sediment, nutrients, pesticides and coliform bacteria in irrigation runoff. There has been some concern about the potential for PAM accumulation to affect microbial ecology. We ran a long-term study applying massive quantities of PAM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 37 publications
1
44
1
3
Order By: Relevance
“…Superabsorbent polymers can inhibit the growth of microorganisms by binding them to soil particles or to themselves, which affects the mobility of microorganism cells and limits their access to carbon dioxide and nutrients (Sojka et al 2006). Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superabsorbent polymers can inhibit the growth of microorganisms by binding them to soil particles or to themselves, which affects the mobility of microorganism cells and limits their access to carbon dioxide and nutrients (Sojka et al 2006). Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…This can be affected by season, employed measures or type of cultivated plant, which additionally impacts other significant variables, e.g. the content of nutrients (Sojka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the N enrichment from the amide groups in PAM, some commercial formulations also contain a few percent additional N, commonly as urea, to promote dissolution on hydration. Environmentally, the small shifts in soil microbial biomass and metabolic potential in the Sojka et al (2006) study were insignificant when weighed against the significant erosion prevention and runoff water quality protection afforded by the use of 5-15 kg PAM ha -1 per season in normal PAM use scenarios, compared to the 2691 and 5382 kg PAM ha -1 applied in their study. In order to apply the amounts of PAM added in their study, even assuming no PAM degradation annually, farmers would need to apply 15-kg active ingredient PAM ha -1 for 180 years to accumulate 2691 kg ha-1 and 360 years to accumulate 5382 kg ha -1 .…”
Section: Pam Effect On Organisms In Runoff and Soilmentioning
confidence: 99%
“…Kay-Shoemake and Watwood (1996) and Kay-Shoemake et al (1998a,b, 2000a reported that although PAM additions to field soils correlate with detectable changes in microbial C utilization, the effects are masked by the influences of other field variables such as crop cover type or nutrient status. Sojka et al (2006) reported the effects of ultrahigh PAM application rates to irrigated soils. Over a 6-year period 1000 kg ha -1 year-1 of a commercial anionic PAM product was added to the soil.…”
Section: Pam Effect On Organisms In Runoff and Soilmentioning
confidence: 99%
“…The anionic charges on PAM solution use cations in the soil to form ion bridges between negatively charged mineral and organic surfaces, thus neutralizing charges, shrinking the electrical double layer and enabling flocculation (Sojka et al 2006). In this way, PAM flocculates, binds and prevents soil particle transport, and restrains occurrence of soil wind erosion.…”
Section: Resultsmentioning
confidence: 99%